Sistem Informasi Deteksi Dini Covid-19 - Bety Etikasari; Trismayanti D. Puspitasari; Arvita A. Kurniasari; Lukie Perdanasari (Jurnal Teknik Elektro dan Komputer, 2020)
Covid-19 has been confirmed as a global pandemic by WHO because of its spread among humans very quickly. WHO announced to do physical distancing as one of the early preventive steps in breaking the chain of Covid-19 spread. Therefore it is necessary to have Information Communication and Community Education (IEC) directly. The purpose of this study is to develop a Covid-19 early detection information system that can be accessed online by the society to make easier on monitoring their own health and get suggestions what must society do and reduce the risk of spread. The application development method use design sprint. The Early Detection Information System displays questions that will be answered by the user as input and display health conditions with suggestions that must be done for handling Covid-19 as output. The results showed that the application can be completed quickly using the design sprint method and applied rule base that has been made with 6 questions and 3 solutions. The validate stage indicated that the application is acceptable for prevent Covid-19.